2022
DOI: 10.3390/geosciences13010007
|View full text |Cite
|
Sign up to set email alerts
|

The Over-Prediction of Seismically Induced Soil Liquefaction during the 2016 Kumamoto, Japan Earthquake Sequence

Abstract: Following the M7.0 strike-slip earthquake near Kumamoto, Japan, in April of 2016, most geotechnical engineering experts believed that there would be significant soil liquefaction and liquefaction-induced infrastructure damage observed in the densely populated city of Kumamoto during the post-event engineering reconnaissance. This belief was driven by several factors including the young geologic environment, alluvially deposited soils, a predominance of loose sandy soils documented in publicly available boring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Identified features were cross-checked using as many pre-event images as possible, aiming to exclude the presence of these features before the earthquake and disqualify possible non-earthquake-related land cover changes. Irrigated crops were especially inspected for the pre-event presence of patterns that can be a source of false positive identifications [72]. These patterns or spots in cropland that could not be validated in the pre-event timeline were excluded from mapping.…”
Section: Visual Mappingmentioning
confidence: 99%
See 1 more Smart Citation
“…Identified features were cross-checked using as many pre-event images as possible, aiming to exclude the presence of these features before the earthquake and disqualify possible non-earthquake-related land cover changes. Irrigated crops were especially inspected for the pre-event presence of patterns that can be a source of false positive identifications [72]. These patterns or spots in cropland that could not be validated in the pre-event timeline were excluded from mapping.…”
Section: Visual Mappingmentioning
confidence: 99%
“…The overall distribution of liquefaction and lateral spreading sites in Amik Plain is strongly correlated to the late Holocene geomorphological conditions as can be seen in Figure 20a. Geomorphological units of Amik Plain [72] that manifested severe liquefaction phenomena were the former Amik Lake and the fluvial valley/levee of Orontes River. Despite modern-era modification of ground surface conditions by large-scale irrigation and drainage works, Holocene and historical geomorphological features can be identified through historical imagery and detailed digital terrain models (Figures 19 and 20b).…”
Section: Correlating the Distance Of Liquefaction Sites With Location...mentioning
confidence: 99%
“…Besides causing deaths, liquefaction in Palu in 2018 caused massive infrastructure damage and huge economic losses [2]. In other places, liquefaction also occurred in Wenchuan China in 2008 [3,4], Kanto Region Japan in 2011 [5], Christchurch New Zealand in 2011 [6], Kumamoto Japan in 2016 [7], Tibetan Plateau China in 2021 [8], and Central Thessaly Greece in 2021 [9].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the sand content has a great impact on the acoustic behavior of the front and back of liquefaction points [16,17,19]. Zeng [20], Heng [21], and Xenaki [22] performed experiments using multifunctional static and dynamic hydraulic shear instruments and developed a linear monotonic correlation between fine contents and pore pressure, and a nonlinear monotonic correlation between clay content and pore pressure [20][21][22][23]. Guo [24], He [25], and Yang [26] investigated the influences of initial consolidation ratio and consolidation stress on the sand strength and liquefaction of sand foundations [24][25][26].…”
Section: Introductionmentioning
confidence: 99%